Organizational Bias in Gender-Based Violence Research. (December 2022) - Weiss, Benjamin R.; Shulman, Mahala
Relatively few victims of gender-based violence (GBV) seek help from nonprofit organizations, healthcare providers, or law enforcement agencies, choosing instead to disclose to friends and family or to nobody at all. This article presents a systematic review of GBV research in sociology showing that, despite low rates of formal service utilization, 68% of published articles use data from organizations including social service providers, hospitals, and police stations and courts. While data from organizations are essential for understanding the experiences of people who report to them, they may not be generalizable to victims broadly. Victims who seek formal help may differ from those who do not in their relative social advantage—along lines of race, socioeconomic status, gender identity, and more—and in their understandings of and responses to violence. We discuss how more non-organizational research might broaden our understanding of violence experienced by society's most marginalized, elucidate ways to make formal organizational responses more inclusive, and sensitize stakeholders in the anti-GBV movement to interventions outside of the therapeutic and carceral state.